Molecular and Phenotypic Profiling for Precision Medicine in Pancreatic Cancer: Current Advances and Future Perspectives - Miyabayashi, Koji; Nakagawa, Hayato; Koike, Kazuhiko (Frontiers in Oncology, 2021)
Pancreatic cancer is the most common lethal malignancy, with little improvement in patient outcomes over the decades. The development of early detection methods and effective therapeutic strategies are needed to improve the prognosis of patients with this disease. Recent advances in cancer genomics have revealed the genetic landscape of pancreatic cancer, and clinical trials are currently being conducted to match the treatment to underlying mutations. Liquid biopsy-based diagnosis is a promising method to start personalized treatment. In addition to genome-based medicine, personalized models have been studied as a tool for testing candidate drugs to select the most efficacious treatment. The innovative three-dimensional organoid culture platform as well as patient-derived xenografts can be exploited for genomic and functional studies at the level of the individual patient for a personalized treatment approach. Combining genome-based medicine with drug screening based on personalized models may fulfill the promise of precision medicine for pancreatic cancer.